The ultimate marketing plan : target your audience! get out your message! build your brand! - Kennedy, Dan S., 1954- (Adams Business, 2011)
As the market place changes under the impact of the rapid transformation of information and the Internet, marketing plans are more important than ever. This title explains how to integrate social media, contacts and membership, and other tools into a complete plan that strengthens your customer base without breaking your budget.